2017
DOI: 10.18203/2320-1770.ijrcog20174432
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in women with stress urinary incontinence following Trans Obturator Tape (TOT) insertion: a prospective study

Abstract: INTRODUCTIONStress urinary incontinence is a symptom or sign indicating that the woman has involuntary loss of urine associated with exertion in the absence of detrusor contraction. It has a significant impact on quality of life. It's prevalence varies from 4% to 35% depending upon the variation in population studied. 1 The treatment options include initial conservative therapies (i.e., lifestyle interventions, pelvic floor muscle training, and bladder training), followed by surgery, which is an option for wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…15 Some other workers who also used KHQ for assessment of quality of life of women undergoing TOT placement also reported high range of improvement over different follow up times, Jacob et al, at six months follow up reported improvement in quality of life of 86.66% women and a reduction of 74.6% in the Part 2 domain of KHQ . 16 Jose et al, who questioned patients with a follow-up range of 7 to 29 months reported a median post-operative KHQ score of 66.66, which is higher than the post-operative KHQ score of patients of our study and could be attributable to difference in population and follow-up period. 17 Nevertheless, almost all the studies have reported that TOT placement brings up to a significantly measurable qualitative change in quality of life of affected patients as observed in present study.…”
Section: Discussioncontrasting
confidence: 83%
“…15 Some other workers who also used KHQ for assessment of quality of life of women undergoing TOT placement also reported high range of improvement over different follow up times, Jacob et al, at six months follow up reported improvement in quality of life of 86.66% women and a reduction of 74.6% in the Part 2 domain of KHQ . 16 Jose et al, who questioned patients with a follow-up range of 7 to 29 months reported a median post-operative KHQ score of 66.66, which is higher than the post-operative KHQ score of patients of our study and could be attributable to difference in population and follow-up period. 17 Nevertheless, almost all the studies have reported that TOT placement brings up to a significantly measurable qualitative change in quality of life of affected patients as observed in present study.…”
Section: Discussioncontrasting
confidence: 83%